2018
DOI: 10.1038/s41586-018-0549-5
|View full text |Cite
|
Sign up to set email alerts
|

The interaction landscape between transcription factors and the nucleosome

Abstract: Nucleosomes cover most of the genome and are thought to be displaced by transcription factors (TFs) in regions that direct gene expression. However, the modes of interaction between TFs and nucleosomal DNA remain largely unknown. Here, we have systematically explored interactions between the nucleosome and 220 TFs representing diverse structural families. Consistently with earlier observations, we find that the majority of the studied TFs have less access to nucleosomal DNA than to free DNA. The motifs recover… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
274
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(295 citation statements)
references
References 59 publications
21
274
0
Order By: Relevance
“…1e). This is in line with published data for the highly homologous ETS domain of SPIB, which showed a clear binding preference for linker and nucleosome entry sites in the NCAP-SELEX assay 19 . These in vitro binding studies suggested that PU.1 alone is indeed restricted by both DNA methylation and chromatin.…”
Section: Pu1 Binding Across Multiple Cell Types In Vivo and In Vitrosupporting
confidence: 92%
“…1e). This is in line with published data for the highly homologous ETS domain of SPIB, which showed a clear binding preference for linker and nucleosome entry sites in the NCAP-SELEX assay 19 . These in vitro binding studies suggested that PU.1 alone is indeed restricted by both DNA methylation and chromatin.…”
Section: Pu1 Binding Across Multiple Cell Types In Vivo and In Vitrosupporting
confidence: 92%
“…A very interesting finding from our work is that the PWWP reader domain can bind across both DNA gyres of the nucleosome. Such cross-gyre binding of nucleosome-interacting proteins was proposed already 25 years ago 44 , but only observed very recently, when a study revealed that transcription factors of the T-box family use such cross-gyre binding 45 . Recent structures of chromatin remodeling enzymes and a retroviral intasome bound to nucleosomes also showed cross-gyre binding through multiple domains [46][47][48][49][50] , but with different geometries and at distinct SHL positions.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, nucleosome displacement actively enforced by chromatin remodelers enables the selective exposure of the fraction of the regulatory information available for transcriptional control in a given cell type (Barozzi et al 2014). Such a process is instructed by sequence-specific DNA-binding proteins able to recognize motifs in nucleosomal DNA (Zhu et al 2018) and instigate nucleosome displacement or remodeling (Zaret and Carroll 2011). While their mode of binding to nucleosomal DNA can be extremely diversified (Zhu et al 2018), such TFs have been collectively termed "pioneers" and coincide at least in part with lineage-determining TFs, whose expression is triggered by microenvironmental cues in the developmental niche of individual tissues.…”
mentioning
confidence: 99%
“…Such a process is instructed by sequence-specific DNA-binding proteins able to recognize motifs in nucleosomal DNA (Zhu et al 2018) and instigate nucleosome displacement or remodeling (Zaret and Carroll 2011). While their mode of binding to nucleosomal DNA can be extremely diversified (Zhu et al 2018), such TFs have been collectively termed "pioneers" and coincide at least in part with lineage-determining TFs, whose expression is triggered by microenvironmental cues in the developmental niche of individual tissues. This is typified by M-CSF (macrophage colony-stimulating factor) induction of the myeloid lineage-determining TF PU.1 in the bone marrow (Mossadegh-Keller et al 2013).…”
mentioning
confidence: 99%